2016
DOI: 10.1155/2016/7852648
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Eighteen-Month Metformin Treatment in Obese Adolescents: Comparison of Results Obtained in Daily Practice with Results from a Clinical Trial

Abstract: Background. In a recent randomized controlled trial (RCT) in obese adolescents, 18 month-treatment with metformin versus placebo was reported to lead to stabilisation of the BMI. This study aimed to compare the effect of metformin on BMI in obese adolescents in daily practice versus results obtained in an RCT. Methods. Obese adolescents treated off label with metformin in daily practice in an outpatient clinic with a follow-up of ≥18 months were identified. Anthropometric and biochemical data were collected at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…As biguanides carry a positive charge, we hypothesize that the increased mitochondrial density in beige iWAT allows the accumulation of these moieties at higher levels than in white iWAT from control mice [36]. Moreover, metformin's activation of HSL at serine 660 in control animals lends further credence to the ability of this drug to suppress obesity in a healthy state [37]. Interestingly, burn alone or metformin treatment did not alter blood glucose levels.…”
Section: Discussionmentioning
confidence: 92%
“…As biguanides carry a positive charge, we hypothesize that the increased mitochondrial density in beige iWAT allows the accumulation of these moieties at higher levels than in white iWAT from control mice [36]. Moreover, metformin's activation of HSL at serine 660 in control animals lends further credence to the ability of this drug to suppress obesity in a healthy state [37]. Interestingly, burn alone or metformin treatment did not alter blood glucose levels.…”
Section: Discussionmentioning
confidence: 92%
“…This finding was also consistent with the results of studies in other single populations. 4,[43][44][45][46] A dose comparison considering the weight loss effect of metformin in obese women with PCOS demonstrated that substantial weight reduction is potentially achievable with high doses of metformin. 47 This result is consistent with the current subgroup analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Metformin is the first-line antidiabetic agent which is primarily used for the treatment of type II diabetes mellitus because of its efficacy and tolerability [16, 17]. In addition, recent studies have shown its anticancer [1820], antitubercular [21, 22], antioxidant properties [2325], and neuroprotective [26] actions.…”
Section: Introductionmentioning
confidence: 99%